History and geography of human genetic diversity III - Cavalli-Sforza, Luigi Luca (Henry Stewart Talks, 2007)
The human genome diversity project (HGDP), Method structure, Limitations of HGDP-CEPH, Are the clusters established by structure "good" races?, Correlation between genetic and geographic distance, Decrease of genetic diversity in the human expansion as serial founder effect, Coevolution of genes and languages, Linguistic families: correlation of the genetic and linguistic trees, Darwin's statement, The complete tree of language evolution
Archived at 2021/02/25